AUGMENTED REALITY IN LEARNING AS AN IMPLEMENTATION OF PROGRESSIVISM EDUCATION IN VOCATIONAL EDUCATION: A LITERATURE REVIEW - Noviani Noviani; Rijal Abdullah; Hendra Hidayat (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze how the application of Augmented Reality (AR) in vocational education represents the principles of progressivism learning and to identify its pedagogical impacts, opportunities, and challenges. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, sixteen relevant research articles published in Sinta 1 and Sinta 2 accredited journals between 2021 and 2025 were systematically reviewed. The findings indicate that AR implementation in vocational education strongly embodies progressivist principles by fostering experiential, student-centered, and technology-integrated learning. AR enhances conceptual understanding, practical skills, and learning motivation while promoting creativity, collaboration, and problem-solving abilities aligned with Dewey’s learning by doing philosophy. Moreover, AR supports contextual and reflective learning environments that prepare students for industrial and technological realities. However, challenges remain in teacher digital competence, development costs, and limited infrastructure. Overall, AR serves as a progressive pedagogical innovation that bridges theory and practice in vocational education, and its transformative potential can be fully realized through systemic readiness, institutional support, and equitable access to digital technology.